Clicked.

Geometry Level 4

sin 6 x + cos 6 x + 1 sin 4 x + cos 4 x + 1 \large \frac{\sin^6x + \cos^6x + 1}{\sin^4x + \cos^4x + 1}

Let the minimum value of the expression above be a a for real x x . Calculate the value of 1 a \dfrac{1}{a} .


The answer is 1.2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Otto Bretscher
Dec 9, 2018

Letting t = sin 2 x t=\sin^2x , we are asked to minimise t 3 + ( 1 t ) 3 + 1 t 2 + ( 1 t ) 2 + 1 = 3 t 2 3 t + 2 2 t 2 2 t + 2 = 3 2 1 2 ( t 2 t + 1 ) \frac{t^3+(1-t)^3+1}{t^2+(1-t)^2+1}=\frac{3t^2-3t+2}{2t^2-2t+2}=\frac{3}{2}-\frac{1}{2(t^2-t+1)} for 0 t 1 0\leq t\leq 1 . The minimum a = 5 6 a=\frac{5}{6} is attained at t = 1 2 t=\frac{1}{2} , when t 2 t t^2-t is minimal. Thus the answer is 1 a = 1.2 \frac{1}{a}=\boxed{1.2} .

Consider

( sin 2 x + cos 2 x ) 3 = sin 6 x + 3 sin 4 x cos 2 x + 3 sin 2 x cos 4 x + cos 6 x Recall sin 2 x + cos 2 x = 1 1 3 = sin 6 x + 3 sin 2 x cos 2 x ( sin 2 x + cos 2 x ) + cos 6 x = sin 6 x + 3 sin 2 x cos 2 x + cos 6 x sin 6 x + cos 6 x = 1 3 sin 2 x cos 2 x Similarly sin 4 x + cos 4 x = 1 2 sin 2 x cos 2 x \begin{aligned} \color{#3D99F6} (\sin^2 x + \cos^2 x)^3 & = \sin^6 x + 3\sin^4 x \cos^2 x + 3\sin^2 x \cos^4 x + \cos^6 x & \small \color{#3D99F6} \text{Recall }\sin^2 x + \cos^2 x = 1 \\ \color{#3D99F6} 1^3 & = \sin^6 x + 3\sin^2 x \cos^2 x {\color{#3D99F6}(\sin^2 x + \cos^2 x)} + \cos^6 x \\ & = \sin^6 x + 3\sin^2 x \cos^2 x + \cos^6 x \\ \implies \sin^6 x + \cos^6 x & = 1 - 3\sin^2 x \cos^2 x & \small \color{#3D99F6} \text{Similarly } \\ \implies \sin^4 x + \cos^4 x & = 1 - 2\sin^2 x \cos^2 x \end{aligned}

Hence we have:

X = sin 6 x + cos 6 x + 1 sin 4 x + cos 4 x + 1 = 2 3 sin 2 x cos 2 x 2 2 sin 2 x cos 2 x = 1 sin 2 x cos 2 x 2 2 sin 2 x cos 2 x = 1 1 2 sin 2 x cos 2 x 2 Since sin 2 θ = 2 sin θ cos θ = 1 1 8 sin 2 2 x 2 \begin{aligned} X & = \frac {\sin^6 x+\cos^6 x+1}{\sin^4 x+\cos^4 x+1} \\ & = \frac {2-3\sin^2 x\cos^2 x}{2-2\sin^2 x\cos^2 x} \\ & = 1 - \frac {\sin^2 x\cos^2 x}{2-2\sin^2 x\cos^2 x} \\ & = 1 - \frac 1{{\color{#3D99F6}\frac 2{\sin^2 x\cos^2 x}}-2} & \small \color{#3D99F6} \text{Since }\sin 2 \theta = 2\sin \theta \cos \theta \\ & = 1 - \frac 1{{\color{#3D99F6}\frac 8{\sin^2 2 x}}-2} \end{aligned}

Note that X X is minimum, when 8 sin 2 2 x 2 \left|\dfrac 8{\sin^2 2x} - 2\right| is minimum. That is when sin 2 2 x = 1 \sin^2 2x = 1 and 8 sin 2 2 x 2 = 6 \left|\dfrac 8{\sin^2 2x} - 2\right|=6 , min ( X ) = 1 1 6 = 5 6 \implies \min(X) = 1 - \dfrac 16 = \dfrac 56 . Therefore, a = 5 6 a=\dfrac 56 1 a = 6 5 = 1.2 \implies \dfrac 1a = \dfrac 65 = \boxed{1.2} .

X X
Dec 9, 2018

sin 6 x + cos 6 x + 1 = ( sin 2 x + cos 2 x ) 3 3 ( cos 4 x sin 2 x + cos 2 x sin 4 x ) + 1 = 2 3 ( sin 2 x + cos 2 x ) sin 2 x cos 2 x = 2 3 ( sin x cos x ) 2 \sin^6x+\cos^6x+1=(\sin^2x+\cos^2x)^3-3(\cos^4x\sin^2x+\cos^2x\sin^4x)+1=2-3(\sin^2x+\cos^2x)\sin^2x\cos^2x=2-3(\sin x\cos x)^2

sin 4 x + cos 4 x + 1 = ( sin 2 x + cos 2 x ) 2 2 sin 2 x cos 2 x + 1 = 2 2 ( sin x cos x ) 2 \sin^4x+\cos^4x+1=(\sin^2x+\cos^2x)^2-2\sin^2 x\cos^2 x+1=2-2(\sin x\cos x)^2

Let ( sin x cos x ) 2 = y (\sin x\cos x)^2=y , then the fraction we have to minimize is equal to 2 3 y 2 2 y \dfrac{2-3y}{2-2y}

y = ( sin x cos x ) 2 = sin 2 ( 2 x ) 4 y=(\sin x\cos x)^2=\dfrac{\sin^2(2x)}4 , so 0 y 1 4 0\le y\le \frac14

Since 2 3 y 2 2 y \dfrac{2-3y}{2-2y} decreases when 0 y 1 4 0\le y\le \frac14 , we just have to put y = 1 4 y=\frac14 to get the minimum which is equal to 5 6 \frac56

sin 6 ( x ) + cos 6 ( x ) + 1 sin 4 ( x ) + cos 4 ( x ) + 1 3 cos ( 4 x ) + 13 2 ( cos ( 4 x ) + 7 ) \frac{\sin ^6(x)+\cos ^6(x)+1}{\sin ^4(x)+\cos ^4(x)+1} \Longrightarrow \frac{3 \cos (4 x)+13}{2 (\cos (4 x)+7)}

Realizing at I could substitute a variable for cos 4 x \cos 4x and restrict that variable's values to the interval [-1,1], then I realized that the expression was increasing through that interval and the minimum would be at the beginning of the interval, I evaluated the expression at that value and received the value of 5 6 \frac56 . Therefore, the desired value is 6 5 \frac65 or 1.2.

Using “keisan Advance Calculator “ in degrees.

x=10, 10, 8, 40<x<50, for minimum.

x= 40,1,50. x=.8333333=n.

1/n=1.2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...